Theory and method in higher education research - Huisman, Jeroen; Tight, Malcolm (Theory and method in higher education research, 2018)
Higher education research is a developing field internationally, which is attracting more and more researchers from a greatvariety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories,methods and methodologies are being applied. This volume of Theory and Method in Higher Education Research contains analyses and discussions of, amongst others, topic modelling, geometric data analysis,creativity and playfulness, longitudinal network analysis, grounded theorymethods and autonetnography.